A novel digital watermarking technique based on ISB (Intermediate Significant Bit) - Zeki, Akram M.; Abdul Manaf, Azizah (World Academy of Science, Engineering and Technology (W A S E T), 2009)
Least Significant Bit (LSB) technique is the earliest developed technique in watermarking and it is also the most simple, direct and common technique. It essentially involves embedding the watermark by replacing the least significant bit of the image data with a bit of the watermark data. The disadvantage of LSB is that it is not robust against attacks. In this study intermediate significant bit (ISB) has been used in order to improve the robustness of the watermarking system. The aim of this model is to replace the watermarked image pixels by new pixels that can protect the watermark data against attacks and at the same time keeping the new pixels very close to the original pixels in order to protect the quality of watermarked image. The technique is based on testing the value of the watermark pixel according to the range of each bit-plane.